The Chlamydia trachomatis IncM Protein Interferes with Host Cell Cytokinesis, Centrosome Positioning, and Golgi Distribution and Contributes to the Stability of the Pathogen-Containing Vacuole - Luís, Maria Pequito (2023)
We thank Irina Franco for critical reading of the manuscript and Agathe Subtil, Guangming Zhong, Ian Clarke, and Joao Paulo Gomes for gifts of antibodies and chlamydial genomic DNA. This work was supported by Fundacao para a Ciencia e a Tecnologia (FCT) in the scope of project UIDB/ 04378/2020 of the Research Unit on Applied Molecular Biosciences, UCIBIO, and LA/P/0140/ 2020 of the Associate Laboratory Institute for Health and Bioeconomy, i4HB. M.P.L. and I.S.P. were supported by PhD fellowships. J.N.B. was supported within the scope of the PhD program Molecular Biosciences (PD/00133/2012), also funded by FCT.